If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(5x-3)=4(3x-6)
We move all terms to the left:
3(5x-3)-(4(3x-6))=0
We multiply parentheses
15x-(4(3x-6))-9=0
We calculate terms in parentheses: -(4(3x-6)), so:We get rid of parentheses
4(3x-6)
We multiply parentheses
12x-24
Back to the equation:
-(12x-24)
15x-12x+24-9=0
We add all the numbers together, and all the variables
3x+15=0
We move all terms containing x to the left, all other terms to the right
3x=-15
x=-15/3
x=-5
| 3c=603 | | 1/4w-5=1-3/4w | | z=(X+(X*Y)/100) | | 3c=602 | | 57+x=37 | | 6x÷5=43 | | (5x-3)(7x+6)=0 | | g+577=962 | | x²+27x-3=0 | | v-160=532 | | v-160=531 | | 7(x+3)=11(x-5) | | 583=u+97 | | -8x+25=2 | | 2(3x-5)+7(x+4)=11(8-7x) | | j+365=560 | | 5x^-11x+12=0 | | X+16+4x=9 | | Y=3x+30(6) | | w-13=639 | | 5r(r-1)+3=0 | | 7÷5x-3÷7x+5=x | | 3(8+4)=4(9+2x) | | 7x²+4x-20=0 | | 15x=9+14 | | 988=s+1 | | X3-4x2+13x=0 | | -1/2y=3/8 | | j-935=54 | | 6/7c=24 | | 16q=208 | | d+238=865 |